Sophronia pseudosagittans sp. nov. (Lepidoptera, Gelechiidae), a new species from the Iberian Peninsula and Tunisia - Bidzilya, Oleksiy V.; Karsholt, Ole; Šumpich, Jan (Zootaxa, 2025)
Sophronia pseudosagittans sp. nov. is described from Portugal, Spain and Tunisia. The morphological and molecular differences between the new species and the closely related S. sagittans Meyrick, 1923 and S. humerella ([Denis & Schiffermüller], 1775) are discussed. Adults and the male and female genitalia of the newly described and related species of Sophronia are illustrated.